Transitional carcinoma with extensive invasion of the bony orbit in a dog - Paiva,S.C.C.S. (2013)
A 12-year-old male English Pointer was examined due to a soft-tissue swelling at the medial canthus of the right orbital region, which was causing facial deformity. The dog had epiphora, purulent nasal discharge, epistaxis, dyspnea, and progressive weight loss. An intraoral mass was observed near the right maxillary premolars. Neoplastic disease was diagnosed based on ancillary tests, which included blood work, skull and intraoral radiographs, ocular ultrasonography and computed tomography. Histopathology revealed transitional carcinoma involving the nasal and oral cavities, maxilla, bony orbit and retrobulbar space. Nasal tumors represent approximately 2% of all tumors diagnosed in this species. Transitional carcinoma is the second most common type of malignant epithelial tumor in the nasal sinuses. This case illustrates the extensive destruction of the soft and bony tissues of the face, including the bony orbit that this type of tumor can cause.